Czysta myśl, nieczyste słowo (Jarosław Iwaszkiewicz – Paul Valéry) - Wójcik, Tomasz (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The title of the article is a quote from a poem by Jarosław Iwaszkiewicz, Do Pawła Valéry (To Paul Valéry), set in the context of other works by the Young Poland author. The paper investigates the two writers’ dialogue as regards the concept of “pure poetry”. Interpreting the poem allows for a reading in the context of the confrontation between two cultural paradigms: Polish and French.